PERAKITAN TEKNOLOGI PRODUKSI PADI ORGANIK BERBASIS PUPUK ORGANIK CAIR DAN PESTISIDA NABATI - Mujiono Mujiono; Tarjoko Tarjoko; Suyono Suyono; Budi Supono Indaryanto (Agroland: Jurnal Ilmu-ilmu Pertanian, 2011)
The aim of this research was to find the culture technology of organic rice production based on liquid organic fertilizer and botanical pesticide with high yield and efficiency. This research was conducted at Purwosari Village, Baturaden Subdistrict, Banyumas Regency, Central Java from August to November 2010. This research was arranged using a Randomized Completely Block Design with seven cultures of organic rice production technology as the treatments. The agronomic variables were plant height, number of tillering, and rice yield (ton/ha). Financial variables were fixed cost, variable cost, and farming revenue. The agronomic variables were analyzed by F test, and if the effect of the treatments were significant the analysis was proceed by Duncan’s Multiple Range Test at 5% level. The financial variable was analyzed using R/C analysis, profit rate analysis, and break even point analysis. Results of the research showed that the assembly of the organic rice production technology which was the most efficient in maintaining high production was the technological assembly with component of straw + cow manure of 5 tons/ha per ha + soil liquid organic fertilizer (LOF) (4 ml/l) + leaf liquid organic fertilizer and botanical pesticide consisting of maja and gadung (6%) + biological agent of Trichoderma harzianum (10 ons per plot) at 2 days after planting with the production level 0f 5.04 tons/ha, and the profit rate of 92.35% and the technological assembly with component of straw + cow manure of 5 tons/ha + soil LOF (4 ml/l) + the combination of leaf LOF + botanical pesticide of maja and gadung (6%) + fermented of palm juice (applied on 45 and 55 days after planting) with the production level of 4.6 tons/ha and the profit rate of 81.73%.